2007
DOI: 10.1016/j.jhydrol.2006.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Aquifer-scale controls on the distribution of nitrate and ammonium in ground water near La Pine, Oregon, USA

Abstract: Summary Geochemical and isotopic tools were applied at aquifer, transect, and subtransect scales to provide a framework for understanding sources, transport, and fate of dissolved inorganic N in a sandy aquifer near La Pine, Oregon. NO 3 is a common contaminant in shallow ground water in this area, whereas high concentrations of NH 4 -N (up to 39 mg/L) are present in deep ground water. N concentrations, N/Cl ratios, tracer-based apparent ground-water ages, N isotope data, and hydraulic gradients indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Subsequent studies in West Bengal showed that DOM originated from the sediments of aquifers (McArthur et al, 2004) and arsenic concentrations corresponded to younger sediments with more biodegradable organic carbon (Postma et al, 2012). In addition, ammonium occurrence in groundwater was related to the release of C and N due to degradation of sedimentary organic matter (SOM) (Hinkle et al, 2007) or OM from buried paleosols of geological age (Glessner and Roy, 2009). Finally, studies of SGD generally ascribed dissolved nutrients (C, N and P) to release from coastal sediments (Gleeson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies in West Bengal showed that DOM originated from the sediments of aquifers (McArthur et al, 2004) and arsenic concentrations corresponded to younger sediments with more biodegradable organic carbon (Postma et al, 2012). In addition, ammonium occurrence in groundwater was related to the release of C and N due to degradation of sedimentary organic matter (SOM) (Hinkle et al, 2007) or OM from buried paleosols of geological age (Glessner and Roy, 2009). Finally, studies of SGD generally ascribed dissolved nutrients (C, N and P) to release from coastal sediments (Gleeson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the local hydrogeology needs to be part of any investigation tracing nitrate origin in groundwater. Considering the time delay between infiltration of nitrate pollution and its appearance in groundwater (Diédhiou et al, 2011;Hinkle et al, 2007), groundwater studies struggle with an appropriate temporal assignment of nitrate contamination. Vice versa, reducing nitrate input affects the groundwater quality only after a certain time lag due to nitrogen turnover processes in soil and the mean transit time of groundwater recharge (Sebilo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies predominantly focus on water chemistry and include topics such as groundwater (redox) zonation and gradients; degree and scale of, and controls on water quality variability and spatial distribution; source apportionment; (bio)geochemical controls on contaminant degradation; reactive transport modelling; aquifer vulnerability mapping; and the determination of background/threshold concentrations (for recent papers, see, e.g. Vissers 2005;Park et al 2006;Hinkle et al 2007;Robins et al 2007;Báez-Cazull et al 2008Hinsby et al 2008;McMahon andChapelle 2007, Sochaczewski et al 2008;Spiteri et al 2008).…”
mentioning
confidence: 99%